2023
DOI: 10.3390/ijms241814339
|View full text |Cite
|
Sign up to set email alerts
|

A Short Review of the Toxicity of Dentifrices—Zebrafish Model as a Useful Tool in Ecotoxicological Studies

Piotr Stachurski,
Wojciech Świątkowski,
Andrzej Ciszewski
et al.

Abstract: This review aims to summarize the literature data regarding the effects of different toothpaste compounds in the zebrafish model. Danio rerio provides an insight into the mechanisms of the ecotoxicity of chemicals as well as an assessment of their fate in the environment to determine long-term environmental impact. The regular use of adequate toothpaste with safe active ingredients possessing anti-bacterial, anti-inflammatory, anti-oxidant, and regenerative properties is one of the most effective strategies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…Ag-NPs are widely known for their strong, broad-spectrum antibacterial activity. Their antibacterial properties are used to control the presence of bacteria in a variety of applications, including dentistry, surgery, and in the treatment of wounds and burns (Chałas et al 2015;Stachurski et al 2023). However, too frequent exposure to products containing nanosilver in sublethal amounts raises widespread concerns that it will lead to the development of silver-resistant microorganisms (Durán et al 2010;Shih et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Ag-NPs are widely known for their strong, broad-spectrum antibacterial activity. Their antibacterial properties are used to control the presence of bacteria in a variety of applications, including dentistry, surgery, and in the treatment of wounds and burns (Chałas et al 2015;Stachurski et al 2023). However, too frequent exposure to products containing nanosilver in sublethal amounts raises widespread concerns that it will lead to the development of silver-resistant microorganisms (Durán et al 2010;Shih et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…had no effect on GH, contrary to that of Stachurski et al (2023). The researchers found that toothpaste formulations inhibited growth factors in zebrafish models.…”
Section: Ogunwole G A; Kolawole Y F; Ayibiowu T E; Oyewole O Amentioning
confidence: 95%
“…Beyond these documented effects, plastic disrupts natural behaviors like algal grazing and can alter endocrine systems and respiration [80,81]. The full picture of chronic plastic exposure remains under investigation, but the combined physical and chemical threats are incontrovertible.…”
Section: Menacing Consequences For Freshwater Faunamentioning
confidence: 99%